INTEGRASI KOMPETENSI DIGITAL DAN TRANSFORMASI MANAJEMEN SUMBER DAYA MANUSIA UNTUK MENDUKUNG PEMBELAJARAN HYBRID DI ERA TRANSFORMASI PENDIDIKAN DIGITAL - Suryanto, Endik; Trihantoyo, Syunu; Rifqi, Ainur (Jurnal Manajemen Pendidikan, 2025)
Integration between educators’ digital competence and human resource management (HRM) is essential in the era of digital transformation and hybrid learning; however, no existing study has clearly formulated such integration. Therefore, the aim of this research is to develop a strategic framework for integrating educators’ digital competence with HRM practices within hybrid learning environments during the digital transformation era. To achieve this objective, the study employs a qualitative approach through a systematic literature review using the PRISMA method. A total of 20 peer-reviewed journal articles published between 2020 and 2025 were analyzed from major databases, including Google Scholar, Scopus, Web of Science, IEEE Xplore, Garuda, and Sinta. The findings indicate that: (1) From the perspective of digital competence, teachers, lecturers, and learners must master pedagogical, reflective, and ethical skills to ensure that technology meaningfully supports the learning process; (2) In terms of HRM transformation, institutions need to strategically utilize artificial intelligence (AI), adopt metaverse-based learning spaces, and implement performance-based incentives; (3) The recommended integration strategy emphasizes synergy among three dimensions: strong individual digital competence, strategic and adaptive HRM, and their alignment within institutional policies and practices.